The influence of plaque composition on underlying arterial wall stress during stent expansion: the case for lesion-specific stents - KELLY, DANIEL; LALLY, CAITRIONA (My University, 2009)
Intracoronary stent implantation is a mechanical procedure, the success of which depends to a large degree on the mechanical properties of each vessel component involved and the pressure applied to the balloon. Little is know about the influence of plaque composition on arterial overstretching and the subsequent injury to the vessel wall following stenting. An idealised finite element model was developed to investigate the influence of both plaque type (hypercellular, hypocellular and calcified) and stent inflation pressures (9, 12 and 15 atm) on vessel and plaque stresses during the implantation of a balloon expandable coronary stent into an idealised stenosed artery. The plaque type was found to have a significant influence on the stresses induced within the artery during stenting. Higher stresses were predicted in the artery wall for cellular plaques, while the stiffer calcified plaque appeared to play a protective role by reducing the levels of stress within the arterial tissue for a given inflation pressure. Higher pressures can be applied to calcified plaques with a lower risk of arterial vascular injury which may reduce the stimulus for in-stent restenosis. Results also suggest that the risk of plaque rupture, and any subsequent thrombosis due to platelet deposition at the fissure, is greater for calcified plaques with low fracture stresses.
PUBLISHED
PMID: 19129001
Keywords: Mechanical & Manufacturing Engineering; Next Generation Medical Devices